Systematics of Pilielmis Hinton, 1971 (Coleoptera: Dryopoidea: Elmidae) - Pinedo-Garcia, Raul Bismarck; Polizei, Thiago Tadeu Silva; Hamada, Neusa; Nascimento, Jeane Marcelle Cavalcante Do (Zootaxa, 2024)
Pilielmis is a small genus of Neotropical Elmidae found in the Amazon basin and French Guiana, with distribution in five countries: Brazil, Colombia, French Guiana, Peru, and Venezuela. Currently, seven species of Pilielmis are known, six of which were described in the original description of the genus by Hinton (1971), and the most recent one was described by Polizei & Barclay (2019). In this paper, we review the genus Pilielmis based on the analysis of type-specimens and material collected in different regions of northern South America. A phylogenetic study was performed to hypothesize the relationship between all species of Pilielmis and to test the monophyly of this genus. For this purpose, 42 morphological characters of adults were investigated, among them some structures that were not illustrated and described in the original descriptions. As result, all seven previously known species were redescribed with standardized morphological information. Three new species were discovered in the examined material: Pilielmis baniwa sp. nov., Pilielmis muricula sp. nov., Pilielmis nheengatu sp. nov. A key for identification of the adults of Pilielmis is proposed and new records for Suriname, Peru, and some Brazilian states are presented. The phylogenetic analysis corroborated the monophyly of Pilielmis and presented phylogenetic information from characteristics not used before in the taxonomy of the genus, such as mouth parts and female ovipositor.